An Insight into Members' Satisfaction with their Union: A Comparative Case Study of Malaysian and American Unions (Malaysian Management Journal, 1999)
This study examines the importance of the various facets of satisfaction with union representation in determining overall satisfaction with the union. samples of union members from Malaysia and the USA are used in this study. generally, overall union satisfaction is specified as function of union members ' expectation concerning union efforts and the perceived outcomes of union performance on (1) 'bread and butter' issues (such as wages and benefits), (2) quality of work issues (such as job interest and workers' voice in the employing organization), and (3) member-union relations (such as the quality of communication between union leaders and members). the results indicate that all the faces are important determinants of overall satisfaction with union representation. however, in the case of WMUPU (Malaysia) the results showed a greater emphasis on aspects like bread and butter, and member-union relations while the OPE1U(USA) findings relate more to issues on quality work life.